Plan De Negocio Para La Creación De Una Empresa De Licor Artesanal A Base De Uchuva (2023)
The purpose of this work is to define a business plan for the creation of a company for the production and marketing of artisanal liquor based on cape gooseberry as the main raw material. This business idea arises in response to the high demand for alcoholic beverages, promoting and emphasizing the recognition of the fruit as it is considered exotic, in addition to being cataloged as an endemic variety of Colombia due to its color, flavor, etc. To promote development in the countryside by generating more employment in the region and improving the conditions of small producers.